Preclosure Fluid Resuscitation Influences Outcome in Gastroschisis - Jansen, Leigh A.; Safavi, Arash; Lin, Yi; MacNab, Ying C.; Skarsgard, Erik D.; null (American Journal of Perinatology, 2012)
Optimal preclosure fluid resuscitation in gastroschisis (GS) is unknown. The purpose of our study was to evaluate effects of preclosure intravenous fluid resuscitation on GS outcome. Cases were accrued from a national GS database. Risk variables analyzed included gestational age (GA), birth weight (BW), neonatal illness severity score, and bolus fluid administration within 6 hours of neonatal intensive care unit admission. Outcomes analyzed included closure success, days of ventilation/total parenteral nutrition (TPN), and bacteremic episodes. Linear and logistic regression analyses were performed. Four hundred seven live-born GS cases were identified (362 with complete resuscitative fluids data). Mean BW, GA, and Score for Neonatal Acute Physiology-II score were 2562 ± 539 g, 36.17 ± 1.95 weeks, and 9.97 ± 12.65, respectively. One hundred sixty-two patients received no supplemental fluid, and 200 patients received a mean of 21.49 (0.81 to 134.81) mL/kg of intravenous fluid. Multivariate outcomes analyses demonstrated a significant, direct relationship between resuscitative volume and days of postclosure ventilation, TPN, length of hospital stay, and bacteremic episodes; specifically, every 17 mL/kg of fluid predicted one additional ventilation day (p = 0.002), TPN day (p = 0.01), and hospital day (p = 0.01) and 0.02 odds increase of an episode of bacteremia (p = 0.03). Judicious, preclosure fluid resuscitation is essential in early GS management. Excessive fluid is associated with several adverse survival outcomes.
Keywords: gastroschisis; outcomes; intravenous fluids; volume expansion